RAQOBAT SHAROITIDA SANOAT KORXONALARI IQTISODIY XAVFSIZLIGINI TAʼMINLASHDA MARKETING VOSITALARIDAN SAMARALI FOYDALANISH YOʻLLARI (Marketing Journal, 2026)
AbstractThis article studies the theoretical, methodological and practical aspects of theeffective use of marketing tools in ensuring the economic security of industrialenterprises in the conditions of an increasingly competitive environment. The studyreveals the essence of the concept of economic security in its inextricable link withmarketing activities, substantiates the importance of such tools as competitiveintelligence, market monitoring, marketing information systems, pricing and productpolicy, segmentation and strategic analysis in enterprises. It also shows the possibilitiesof improving the quality of management decisions, early detection of external and internal threats, and rational use of resources through the systematic collection,processing and analysis of marketing information.Keywords: competitive intelligence, enterprises, economic and financial securityof enterprises, risks, strategic stability.